Aktivitas Antijamur Ekstrak Aseton Daun Teratai Putih (Nymphae alba) Terhadap Jamur Candida albicans - Ade Irawan; Mariam Ulfah; Teguh Adiyas Putra (BEST Journal (Biology Education, Sains and Technology), 2023)
Indonesia is a tropical country with very diverse plants. This plant is a source of secondary metabolite compounds that have pharmacological activities that combine a variety of them including antifungal. One of them is the white lotus (Nymphae alba). This plant contains flavonoids, phenols, terpenoids and alkaloids. This plant also has pharmacological activities including antioxidant, antiobesity, analgesic and antidiarrheal. This study aims to determine the inhibition zone of white lotus acetone extract (N.alba) against the fungus Candida albicans. The extraction process was carried out by maceration method with acetone solvent for 3 x 24 hours. The antifungal test method was carried out using the disc diffusion method, three concentrations of acetone extract were used, 25%, 50% and 75%, the positive control used was ketoconazole and the negative control was 10% DMSO. The results of this study were white lotus acetone extract which had an inhibition zone value of 11.8 mm for the extract with a concentration of 25% in the strong category, 14 mm for the extract with a concentration of 50% in the strong category, and 16.3 mm for the extract with a concentration of 75 % in the strong category, while the positive control has an inhibition zone value of 10 mm. This proves that white lotus has good potential as an antifungal agent from plant.